Antimicrobial activity of ethanolic extract of Usnea longissima - B, Thippeswamy; Naveenkumar, K J; Bodharthi, J Guruprasad; Shivaprasad, S R (Journal of Experimental Sciences, 2012)
Introduction: Usnea Longissima is an epiphyte species of lichen belongs to the family Parmeliaceae. Lichenic acids isolated from Usnea Longissima are growth inhibitors. Usnea Longissima was used a dermatological aid for during wounds in the pecific North West. Methods: The ethanol extract of Usnea Longissima were screened for potential antibacterial activity and antifungal activity using Agar well diffusion method against six infectious strains and two dermatophytic fungi Trichoderma viride and Candida albicans. Results: Ethanol extract of Usnea Longissima exhibited significant antibacterial activity and antifungal activity with 1mg/ml Agar well diffusion method against the Gram positive Staphylococcus aureus (26 ± 0.5), and Gram negative Pseudomonas aeruginosa (18 ± 0.5), Klebsiella pneumoniae (21 ± 0.5), Shigella dysenteriae (10 ± 0.3), Salmonella typhi (14 ± 0.5), Escherichia coli (-) and two dermatophytic fungi Trichoderma viride (14 ± 0.5) and Candida albicans (11 ± 0.5). Conclusion The present study is justified the traditional use and the effect of ethanol extract of lichen Usnea longissima was screened their level of antimicrobial potential.